INTEGRASI JUBELIO DENGAN DYNAMICS 365 BUSINEES CENTRAL MODUL PURCHASE BAGIAN VENDOR DAN PURCHASE ORDER SECTION: Jubelio Integration with Dynamics 365 Business Central Sales Module for the Product and Product Stock - Nur Aziezah; Arinda Choiris Dea Salsabela; Walidatush Sholihah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2023)
Companies use Enterprise Resource Planning (ERP) to integrate their business processes. One of the ERP applications is ERP Dynamics 365 Business Central. The method of transferring product and product stock data from Jubelio Omnichannel to ERP Dynamics 365 Business Central is still being done manually. This study integrates the Dynamics 365 ERP application with Jubelio Omnichannel to help process transactions. Integration between the two applications is made by adding the following features: automatic addition of product data from Jubelio Omnichannel to Dynamics 365 Business Central, creating an automatic product data transfer feature from Jubelio Omnichannel to Dynamics 365 Business Central, post adjustment feature to adjust product stock data from Dynamics 365 Business Central to Jubelio Omnichannel automatically, as well as the all adjustment feature for automatic withdrawal of product stock data from Jubelio Omnichannel to Dynamics 365 Business Central. The integration process also aims to make the product and product stock data formats from Jubelio match the data formats in Dynamics 365 Business Central. This research was conducted using the Scrum methodology. After integration, existing product data on Jubelio Omnichannel can be entered into Dynamics 365 Business Central items. In addition, inventory adjustments (post adjustments) can be made from Dynamics 365 Business Central to Jubelio Omnichannel. Transaction data from Jubelio can be directly pulled into Dynamics 365 Business Central. ABSTRAK Perusahaan menggunakan Enterprice Resource Planning (ERP) untuk mengintegrasikan proses bisnisnya, salah satu contohnya adalah ERP Dynamics 365 Business Central. Saat ini, proses pemindahan data product dan product stock dari Jubelio Omnichannel ke ERP Dynamics 365 Business Central masih dilakukan secara manual. Namun, penelitian ini bertujuan untuk mengintegrasikan aplikasi ERP Dynamics 365 dengan Jubelio Omnichannel untuk mempermudah proses transaksi. Hal ini dilakukan dengan menambahkan beberapa fitur, seperti penambahan data product secara otomatis dari Jubelio Omnichannel ke Dynamics 365 Business Central, transfer data product secara otomatis dari Jubelio Omnichannel ke Dynamics 365 Business Central, post adjustment untuk penyesuaian data product stock dari Dynamics 365 Business Central ke Jubelio Omnichannel secara otomatis, serta all adjustment untuk penarikan data product stock secara otomatis dari Jubelio Omnichannel ke Dynamics 365 Business Central. Tujuan dari proses integrasi ini adalah agar format data product dan product stock dari Jubelio sesuai dengan format data pada Dynamics 365 Business Central. Penelitian ini menggunakan metodologi Scrum. Setelah proses integrasi selesai, data product dari Jubelio Omnichannel dapat masuk ke item Dynamics 365 Business Central dan dilakukan penyesuaian persediaan dari Dynamics 365 Business Central ke Jubelio Omnichannel. Selain itu, data transaksi dari Jubelio dapat langsung ditarik ke Dynamics 365 Business Central.